Emissivity evaluation of human enamel and dentin - Lancaster, P. E.; Carmichael, F. A.; Clerehugh, V.; Brettle, D. S. (Frontiers in Physiology, 2022)
Background Human enamel and dentin temperatures have been assessed with non-contact, infra-red imagine devices for safety and diagnostic capacity, and require an emissivity parameter to enable absolute temperature-measurements. Emissivity is a ratio of thermal energy emitted from an object-of-interest, compared to a perfect emitter at a given temperature and wavelength, being dependent on tissue-composition, structure and surface-texture. Evaluating emissivity of human enamel and dentin is varied and warrants review. The primary aim was to evaluate emissivity of the external and internal surface of human enamel and dentin, free from acquired or developmental defects, against a known reference-point. The secondary aim was to assess the emissivity-value of natural caries in enamel and dentin. Method Fourteen whole molar teeth were paired within a thermally-stable chamber at 30oC. Two additional teeth (one sound and one with natural occlusal caries – ICDAS caries score 4 and radiographic score RB4) were prepared into 1mm-thick slices and placed on a hotplate at 30oC within the chamber. 3M Scotch Super 33+ Black Vinyl Electrical Tape was the emissivity-reference-point (0.96). All samples reached thermal equilibrium and a FLIR SC305 Infra-red Camera recorded the warming sequence. Emissivity-values were calculated using the Tape reference-point and thermal camera software. Results External enamel-surface mean emissivity-value was 0.96 (SD 0.01, 95% CI 0.96-0.97) whereas, internal enamel-surface was 0.97 (SD 0.01, 95% CI 0.96-0.98). Internal crown-dentin mean emissivity-value was 0.94 (SD 0.02, 95% CI 0.92-0.95), whereas internal root-dentin was 0.93 (SD 0.02, 95% CI 0.91-0.94) and surface root-dentin had a value of 0.84 (SD 0.04, 95% CI 0.77-0.91). Internal enamel-surface with caries mean emissivity-value was 0.82 (SD 0.05, 95% CI 0.38-1.25) and internal crown-dentin with caries was 0.73 (SD 0.08, 95% CI 0.54-0.92). Conclusion Emissivity-values of sound enamel, both internal and external were similar and higher than all sound dentin types in this study. Sound dentin emissivity-values diminished from the crown, to root and root surface. The lowest emissivity-values were recorded in caries lesions of both tissues. This methodology can improve emissivity acquisition for comparison of absolute temperatures between studies which evaluate thermal safety during dental procedures and may offer a caries diagnostic aid.